Enhanced siRNA Delivery and Selective Apoptosis Induction in H1299 Cancer Cells by Layer-by-Layer-Assembled Se Nanocomplexes: Toward More Efficient Cancer Therapy - Sharifiaghdam, Maryam; Shaabani, Elnaz; Sharifiaghdam, Zeynab; De Keersmaecker, Herlinde; De Rycke, Riet; De Smedt, Stefaan; Faridi-Majidi, Reza; Braeckmans, Kevin; Fraire, Juan C. (Frontiers in Molecular Biosciences, 2021)
Nanotechnology has made an important contribution to oncology over the past several decades, especially for drug delivery. While many different nano-delivery systems have been suggested for cancer therapy, selenium nanoparticles (SeNPs) are particularly promising anti-cancer drug carriers as their core material offers interesting synergistic effects to cancer cells. Se compounds can exert cytotoxic effects by acting as pro-oxidants that alter cellular redox homeostasis, eventually leading to apoptosis induction in many kinds of cancer cells. Here we report on the design and synthesis of novel layer-by-layer Se-based nanocomplexes (LBL-Se-NCs) as carriers of small interfering RNA (siRNA) for combined gene silencing and apoptosis induction in cancer cells. The LBL-Se-NCs were prepared using a straightforward electrostatic assembly of siRNA and chitosan (CS) on the SeNP’s solid core. In this study, we started by investigating the colloidal stability and protection of the complexed siRNA. The results show that CS not only functioned as an anchoring layer for siRNA, but also provided colloidal stability for at least 20 days in different media when CS was applied as a third layer. The release study revealed that siRNA remained better associated to LBL-Se-NCs, with only 35% release after 7 days, as compared to CS-NCs with 100% siRNA release after 48 hours, making the LBL nanocarrier an excellent candidate as an off the shelf formulation. When applied to H1299 cells, it was found that they can selectively induce around 32% apoptosis while significantly less apoptosis (5.6%) was induced in NIH/3T3 normal cells. At the same time they were capable of efficiently inducing siRNA downregulation (35%), without loss of activity 7 days after synthesis. We conclude that LBL-Se-NCs are promising siRNA carriers with enhanced stability and with a dual mode of action against cancer cells.